Implementasi Program Jaminan Kesehatan Nasional terhadap Pelayanan Promotif dan Preventif di Puskesmas Kutalimbaru Kota Medan - Wuni Barokah; Nur Cahaya Hasibuan; Fitriani Pramita Gurning (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
This study discusses the implementation of the National Health Insurance Program (JKN) in improving promotive and preventive services at the Kutalimbaru Health Center in Medan City. The main focus of the study is how the JKN program supports health prevention and promotion efforts through capitation fund management, the role of health workers, and community and cross-sector involvement. Data were obtained through interviews with JKN program holders and patients, and supported by literature studies from various scientific journals. The results of the study indicate that the JKN program has made a positive contribution to strengthening promotive and preventive services, although there are still obstacles such as limited resources, less than optimal community participation, and fund management that needs to be more transparent and efficient. The main recommendations include increasing the capacity of health workers, strengthening cross-sector collaboration, and utilizing information technology to expand the reach of health education. This study emphasizes the importance of integrating promotivepreventive programs in the JKN system to achieve quality and sustainable Universal Health Coverage (UHC).